Profile Reconstruction Utilizing Forward-Backward Time-Stepping With the Integration of Automated Edge-Preserving Regularization Technique for Object Detection Applications - Yong, G.; Ping, K.A.H.; Sahrani, S.; Marhaban, M.H.; Sariphan, M.I.; Moriyama, T.; Takenaka, T. (Electromagnetics Academy, 2017)
A regularization is integrated with Forward-Backward Time-Stepping (FBTS) method which is formulated in time-domain utilizing Finite-Difference Time-Domain (FDTD) method to solve the nonlinear and ill-posed problem arisen in the microwave inverse scattering problem. FBTS method based on a Polak-Ribiète-Polyak conjugate gradient method is easily trapped in the local minima. Thus, we extend our work with the integration of edge-preserving regularization technique due to its ability to smooth and preserve the edges containing important information for reconstructing the dielectric profiles of the targeted object. In this paper, we propose a deterministic relaxation with Mean Square Error algorithm known as DrMSE in FBTS and integrate it with the automated edge-preserving regularization technique. Numerical simulations are carried out and prove that the reconstructed results are more accurate by calculating the edge-preserving parameter automatically.